40.0k views
3 votes
F(x)=−10x2−x and g(x)=−2x2−x, find (f−g)(x) and (f−g)(−2)

User Oleg Rybak
by
4.3k points

1 Answer

6 votes

Answer:

(f - g)(x) = -8x²

(f - g)(2) = -32

General Formulas and Concepts:

Algebra I

  • Combining like terms

Explanation:

Step 1: Define

f(x) = -10x² - x

g(x0 = -2x² - x

(f - g)(x) is f(x) - g(x)

(f - g)(2) is f(2) - g(2)

Step 2: Find (f - g)(x)

  1. Substitute: (f - g)(x) = -10x² - x - (-2x² - x)
  2. Distribute -1: (f - g)(x) = -10x² - x + 2x² + x
  3. Combine like terms: (f - g)(x) = -8x²

Step 3: Evaluate

  1. Substitute: (f - g)(2) = -8(-2)²
  2. Evaluate: (f - g)(2) = -8(4)
  3. Multiply: (f - g)(2) = -32

And we have our answers!

User Xingbin
by
4.7k points